Дослідження готовності майбутніх фахівців соціальної сфери до неформальної освіти - Петровська, Катерина Володимирівна (ХНУ, 2022)
У тезах подано результати дослідно-експериментальної роботи щодо дослідження ступеню готовності майбутніх фахівців соціальної сфери до неформальної освіти.
Study of the readiness of future specialists in the social sphere for non-formal education
The theses present the results of research and experimental work on the study of the degree of readiness of future specialists in the social sphere for non-formal education.
Keywords: неформальна освіта; готовність; заклад вищої освіти фахівці соціальної сфери; Non-formal education; readiness; institution of higher education; specialists in the social sphere